Women’s Leadership in Indonesian Islamic Educational Institutions: A Systematic Literature Review - Maulidiya Maulidiya; Tri Wahyudi Ramdhan; Mufaizin Mufaizin (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to examine women’s leadership in Islamic educational institutions in Indonesia through a systematic literature review. It focuses on synthesizing previously fragmented and context-specific research to provide a more coherent understanding across institutional settings and sociocultural contexts. Methods – This study employed a Systematic Literature Review (SLR) to examine patterns of women’s leadership and gender dynamics in Islamic educational institutions in Indonesia. Using the PRISMA framework, this review analyzes 30 peer-reviewed articles published between 2020 and 2025. The analysis employs thematic synthesis to identify patterns in leadership models, structural dynamics, and institutional outcomes. Findings – The findings reveal that women’s leadership is multidimensional, encompassing religious-charismatic, managerial-professional, and emerging digital forms. The findings indicate that while structural barriers such as patriarchal norms and institutional hierarchies remain significant, they are not absolute. Women leaders actively negotiate these constraints through adaptive and context-sensitive strategies. As a result, leadership should be understood as a dynamic process shaped by the interplay between structure and agency. Research Implications – This research contributes a structured synthesis that serves as a basis for more context-sensitive research and policy development, offering a clearer framework for understanding female leadership within the landscape of Islamic education.